Regime of National Forest Policy and the North East India - Varah, Franky; Pamreishang, C.; Shimrah, Tuisem (Indian Forester, 2019)
The present Forest Policy of India is derived from the National Forest Policy of 1952. It targeted 33% forest cover throughout India, and 60% forest cover in mountainous and hill regions of the country. This objective was reiterated in the National Forest Policy of 1988 and confirmed in the National Forestry Commission Report of 2006. The North East India is rich in biological and cultural diversity, and as such the majority of the states in the region met the prescribed policy norms. In fact, the North Eastern states of India have the potential for more afforestation. However, according to the recent Forest Survey of India Report, the North Eastern states have had the highest loss of forest in India in recent times. This paper argues that the reason for forest loss is most likely just a tip of the iceberg. In the ground reality, there are a lot of reasons for the loss of forest that include among other issues; the questions of ownership rights, forest policies, poverty, and development activities. The study has shown that forest policy not only infringed upon the peoples’ rights but also contributed to forest degradation.